Effects of Prompting in Reflective Learning Tools: Findings from Experimental Field, Lab, and Online Studies - Renner, Bettina; Prilla, Michael; Cress, Ulrike; Kimmerle, Joachim (Frontiers in Psychology, 2016)
Reflective learning is an important type of learning both in formal and informal situations—in school, higher education, at the workplace, and in everyday life. People may benefit from technical support for reflective learning, in particular when supporting each other by reflecting not only upon their own but also upon other people’s problems. We refer to this collective approach where people come together to think about experiences and find solutions to problems as “collaborative reflection”. We present three empirical studies about the effects of prompting in reflective learning tools in such situations where people reflect on others’ issues. In Study 1 we applied a three-stage within-group design in a field experiment, where 39 participants from two organizations received different types of prompts while they used a reflection app. We found that prompts that invited employees to write down possible solutions led to more comprehensive comments on their colleagues’ experiences. In Study 2 we used a three-stage between-group design in a laboratory experiment, where 78 university students were invited to take part in an experiment about the discussion of problems at work or academic studies in online forums. Here we found that short, abstract prompts showed no superiority to a situation without any prompts with respect to quantity or quality of contributions. Finally, Study 3 featured a two-stage between-group design in an online experiment, where 60 participants received either general reflection instructions or detailed instructions about how to reflect on other people’s problems. We could show that detailed reflection instructions supported people in producing more comprehensive comments that included more general advice. The results demonstrate that to increase activity and to improve quality of comments with prompting tools require detailed instructions and specific wording of the prompts.